Police response to mental health calls for service: gatekeepers and street corner psychiatrists - Jachimowski, Kayla G. (Policing perspectives and challenges in the twenty-first century, 2021)
An introduction to the problem -- Understanding mental health: A brief history of American practice -- Mental health's implications for policing -- State of policing and mental health calls for service -- Police training - general patterns related to CIT -- Police training - a more detailed look -- Moving forward: theory and practice.